EVALUATION OF A RAPID TEST TO DETECT CARBAPENEMASE PRODUCTION AMONG GRAM-NEGATIVE BACILLI. - Nagalapuram, Vishnu; J, Jayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: There is a need for an early detection of carbapenemase-producing Gram-negative bacilli to reduce the morbidity and mortality associated with it. The objective of this study is to evaluate the usefulness of the Carba NP test in detecting carbapenemase-producing Gram-negative bacilli. Methods: This prospective experimental study was conducted in 2013 at PSG Institute of Medical Sciences and Research, Coimbatore. In this study, 120 consecutive Gram-negative bacilli clinical isolates identified as carbapenem resistant as per the Clinical and Laboratory Standard Institute guidelines were subjected to Carba NP. Results: About 62.5% of the carbapenem-resistant isolates were found to be carbapenemase producers by modified Hodge test. The sensitivity of the Carba NP test was found to be 92% and the specificity was 100%. The most common bacterial isolate was Acinetobacter baumannii, and the most common sample was urine. Conclusion: The Carba NP test is a simple inexpensive, rapid, reproducible, sensitive test that can be performed directly from the colonies. It improves early detection of patients infected or colonized with carbapenemase in the hospital.